THE EFFECTIVENESS OF TASK-BASED LEARNING IN IMPROVING SPEAKING SKILLS AMONG EFL LEARNERS IN UZBEKISTAN - Gavhar Zuhriddinova (Scholar Express Journal, 2025)
This paper explores the effectiveness of Task-Based Language Teaching (TBLT) in developing speaking competence among English as a Foreign Language (EFL) learners in Uzbekistan and in wider global contexts. Drawing upon both theoretical perspectives and classroom-based observations, the study analyses how task-based instruction promotes communicative competence, learner engagement and fluency in diverse proficiency groups. It also considers the challenges of implementing TBLT in Uzbek educational institutions, where traditional grammar-focused instruction and examoriented attitudes still dominate. The findings suggest that while TBLT is highly effective for developing real-life communication skills, its success depends on teacher training, appropriate task design and institutional support. The paper concludes by highlighting pedagogical implications for both school and university contexts in Uzbekistan and provides recommendations for integrating TBLT more effectively within national curricula.
Keywords: Task-Based Learning; speaking skills; EFL; Uzbekistan